Studies on Heterosis and its Extent for Horticultural Traits in Long Melon (Cucumis melo var. flexuosus (L.) Naudin) - C, Chaithra; Sood, Meenakshi; K. M, Indiresh; M, Anjanappa; Kattegoudar, Jyothi; R., Rajeshwari (International Journal of Bio-resource and Stress Management, 2022)
A study was conducted to assess the extent of heterosis for various horticultural traits in long melon at College of Horticulture, Kolar, Karnataka, India. In the present study, 18 cross combinations of long melon were developed by crossing six female lines with three male lines in L×T mating design. The F1 combinations were evaluated along with nine parental lines to study heterosis for earliness, growth, yield and yield attributing traits. The F1 LM3×Arka Sheetal took minimum number of days for 50% female flower anthesis and exhibited maximum negative heterobeltiosis (-3.75%) for this trait. Six out of eighteen cross combinations showed significant negative heterosis over the better parent for the days to first harvest with the cross LM3 × JK Special showing highet value (-5.18%). High values of heterosis coupled with favourable per se values for male to female flower ratio were observed in LM11×Punjab Long melon-1 (-12.99%) and LM10×Arka Sheetal (-22.08%). The extent of heterosis over better parent was found as high as 59.44 % for fruit yield per vine in the cross LM 3×ArkaSheetal. This cross along with LM 9×Punjab Long melon-1, LM 15×Arka Sheetal and LM 3×J K Special were found to be the best crosses for yield and contributing traits exhibiting highest heterobeltiosis coupled with high per se values, and may be explored further for the development of promising genotypes. The highest yielding F1 combinations in present study involved at least one poor to average yielding parent, suggesting that simple dominance components might have lead to expression of heterosis.